Knowledge, attitude, practice, and factors associated with prevention practice towards COVID-19 among healthcare providers in Amhara region, northern Ethiopia: A multicenter cross-sectional study. - Wassachew Ashebir; Belete Yimer; Atsede Alle; Muluken Teshome; Yohannes Teka; Awraris Wolde (Public Library of Science (PLoS), 2022)
Healthcare providers (HCPs) are at an increased risk of getting COVID-19 as a result of their front-line works. Health behaviors of HCPs can influence prevention and control actions implemented in response to the pandemic. Hence, this study aimed to assess the knowledge, attitude, and practice (KAP) and factors associated with prevention practice towards COVID-19 among healthcare providers in Amhara region, northern Ethiopia. A multicenter cross-sectional study was conducted among 422 HCPs in selected public health facilities of Amhara region, between 20th September and 20th October 2020. Data related to HCP's KAP and socio-demographic characteristics were collected using a pre-tested self-administered questionnaire. Bloom's cut-off ≥ 80%, ≥90%, and ≥75% was used to determine adequate knowledge, positive attitude, and good prevention practice, respectively. Data were analyzed using SPSSS version 25.0. A multivariable logistic regression analysis was performed to identify factors significantly associated with COVID-19 prevention practice. Statistical significance was determined at a p-value of < 0.05 and the presence of association was described using odds ratio (OR) with their 95% confidence interval (CI). Overall, 368 (89.8%), 387 (94.4%), and 326 (79.5%) HCPs had adequate knowledge, positive attitude, and good prevention practice towards COVID-19, respectively. Factors significantly associated with good COVID-19 prevention practice were being a Nurse in profession (AOR = 2.13, 95% CI = 1.13-3.99), having < 5 years of working experience (AOR = 0.46, 95% CI = 0.24-0.86), using social media (AOR = 6.20, 95% CI = 2.33-16.51) and television and or radio (AOR = 4.03, 95% CI = 1.56-10.38) as sources of COVID-19 information. HCPs had adequate knowledge, positive attitude and good prevention practice towards COVID-19. Being a Nurse, having < 5 years of working experiences, using social media and television and or radio were factors associated with good prevention practice. Thus, developing HCP's professional carrier through training opportunities, sharing experiences and using verified information sources are crucial to better improve COVID-19 prevention practice.